Observational constraints to the dynamics of dust particles in the coma of comet 67P/Churyumov–Gerasimenko. Issue 4 (26th April 2021) - Frattin, E; Bertini, I; Ivanovski, S L; Marzari, F; Fulle, M; Zakharov, V V; Moreno, F; Naletto, G; Lazzarin, M; Cambianica, P; Cremonese, G; Ferrari, S; et al.
ABSTRACT: In this work, we aim to characterize the dust motion in the inner coma of comet 67P/Churyumov–Gerasimenko to provide constraints for theoretical 3D coma models. The OSIRIS camera on-board the Rosetta mission was able for the first time to acquire images of single dust particles from inside the cometary coma, very close to the nucleus. We analyse a large number of particles, performing a significant statistic of their behaviour during the post-perihelion period, when the spacecraft covered distances from the nucleus ranging between 80 and 400 km. We describe the particle trajectories, investigating their orientation and finding highly radial motion with respect to the nucleus. Then, from the particle brightness profiles, we derive a particle rotational frequency of ν < 3.6 Hz, revealing that they are slow rotators and do not undergo fragmentation. We use scattering models to compare the observed spectral radiance of the particles with the simulated ones in order to estimate their size, finding values that range from millimetres up to centimetres. The statistics performed in this paper provide useful parameters to constrain the cometary coma dynamical models.